Maqashid Syariah sebagai Framework Kebijakan Fiskal: Integrasi Nilai Islam dalam Public Finance - Ana Muthoharoh; Cantika Sundari Wijaya; Dian Putri Lestari; Erda Nur Fitria; Amalia Nuril Hidayati (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study examines how Maqashid Syariah can serve as a framework for formulating fiscal policy that is more oriented toward public welfare and social justice. The problem addressed is the limited integration of Islamic values—particularly the principle of maslahah and the five essential objectives of Maqashid Syariah—into modern fiscal policy, which remains dominated by secular approaches. The research employs a literature review method by analyzing relevant books, scholarly articles, and prior studies on maqashid, maslahah, and public finance policy. The results indicate that the concepts of dharuriyyat, hajiyyat, and tahsiniyyat can provide a foundation for prioritizing state revenue and expenditure management. The discussion highlights that integrating Islamic values enables fiscal policy to become more just, efficient, and welfare-oriented. The study concludes that Maqashid Syariah is a relevant framework to strengthen the direction of modern fiscal policy.